ANALISIS DAYA SAING PRODUK PERTANIAN INDONESIA TAHUN 1990—2002 - Novitasari, Atika; Ma'ruf, Ahmada (Jurnal Ekonomi & Studi Pembangunan, 2004)
Nowadays, globalization and economic integration process have accelerated because of liberalization and change in technology on many fields, and then influence to international acceleration of production and distribution. The development of international market is very influent an alternative of domestic policy whether on production or price. In this era, industry competitiveness is important to be done, so a country will get value added from this globalization.For increasing competitiveness, a country have to choose a sector and a commodity that has a competitive advantage which will be developed. By using a Revealed Competitive Advantage (RCA), it hoped can be improve the competitiveness of Indonesia. Agricultural products especially a fishery and a forestry commodities, and an export of an agricultural commodities are the commodities which can be expected. The result of this paper shows that the Indonesian agricultural products in 1990-2002 have a high competitive advantage especially fishery products.